The Existence and Role of Indigenous Leadership in Local Governance: A Systematic Review of Indonesian Case Studies - Wance, Marno; Layn, Safrudin Bustam; Collins, James T.; Syahidah, Ummu (Journal of Government Science Studies, 2025)
This research aims to analyze the distribution of studies related to customary leadership and local governance in Indonesia, which includes the distribution of articles per year, types of research, research targets, distribution by province and district in Maluku, as well as the fields of science used. The method used is a systematic review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach to filter and select relevant articles. The analysis results show that the trend of publishing articles on customary leadership increased, peaking in 2022, but declined in the following years. The type of research is dominated by qualitative and normative legal approaches, indicating the need for in-depth analysis and regulatory strategies in understanding the role of customary leadership. The research targets focus on customary leadership and local government, reflecting the importance of these two elements in local governance. In terms of region, Maluku, particularly Central Maluku Regency, is the primary focus of the research, followed by Bali, South Sulawesi, and Central Java. Field analysis shows that this research is primarily reviewed from the perspectives of legal science, governance science, sociology, and anthropology, reflecting the complexity of studying traditional leadership from legal, social, and cultural aspects. These findings indicate that conventional leadership plays a significant role in maintaining cultural identity and social stability but also faces challenges in adapting to formal regulations. This research opens up opportunities for more in-depth studies in less accessible areas and with a richer multidisciplinary approach.